Adaptasi dan Validasi Skala Normalisasi Kekerasan Seksual terhadap Korban Laki-Laki: Pendekatan Analisis Faktor Eksploratori dan Konfirmatori - Dwi Endrasto Wibowo; Arbain Fajar Andi Hamid; Muh. Fahmi Anugerah (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2026)
The normalization of sexual violence against male victims is a phenomenon that has not received adequate empirical attention in Indonesia, including a lack of psychometrically valid measurement instruments. This study aims to adapt and validate the Male Rape Myth Acceptance Scale (MRMAS) for the Indonesian context. A total of 16 items were adapted through forward translation, back-translation, and expert review (S-CVI/Ave = 0.91), then administered to 358 active university students. EFA analysis yielded a two-factor structure consisting of Victim Blaming (10 items) and Victim Disbelief (4 items), explaining 50.7% of the total variance.